ANALISIS HIRARKI PROSES UNTUK PENGEMBANGAN MINYAK ATSIRI - djawardi, djawardi (Jurnal Sains dan Teknologi Indonesia, 2012)
Indonesia is rich with diversity / germplasm aromatic plants that produce essential oils. Essential oils also called etheric oils, or oil fly. There is a non-oil export commodities are needed in various industries. The many types of Essential Oils require handling a priority scale. The method used is Analysis Hierarchy Process (AHP) by utilizing the expert judgement. The analysis using criteria Feasibility for SMEs, New Commodities and the New Territories, and sub-criteria Speed of Capital Returns, Market Prospects, Easy Access Resource, Value Added, and Enviroment. Based on criteria and sub-criteria results that essential oils of Jasmine (Melati), Masoyi (Masoyi) and Cubeb (Kemukus) must be prioritized to development.